2020
DOI: 10.1038/s41598-020-62563-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing photoluminescence of carbon quantum dots doped PVA films with randomly dispersed silica microspheres

Abstract: As a kind of excellent photoluminescent material, carbon quantum dots have been extensively studied in many fields, including biomedical applications and optoelectronic devices. They have been dispersed in polymer matrices to form luminescent films which can be used in LEDs, displays, sensors, etc. Owing to the total internal reflection at the flat polymer/air interfaces, a significant portion of the emitted light are trapped and dissipated. In this paper, we fabricate free standing flexible PVA films with pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Recently, carbon materials have been given great importance as nanofillers in the preparation of functional polymer nanocomposites to improve the properties of PVA films. , Sapalidis et al have produced PVA nanocomposite films containing dendritic polymer (QPEI)-functionalized multi-walled carbon nanotubes (oxCNTs) using various oxCNT QPEI contents ranging from 0.05 to 1.0% w/w and reported that these films exhibited enough optical transparency, advanced mechanical properties, and exceptionally high antibacterial behavior . Kovalchuk and co-workers have produced luminescent PVA composite films containing coal-derived graphene quantum dots (GQDs) by a simple and environmentally friendly solution method.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, carbon materials have been given great importance as nanofillers in the preparation of functional polymer nanocomposites to improve the properties of PVA films. , Sapalidis et al have produced PVA nanocomposite films containing dendritic polymer (QPEI)-functionalized multi-walled carbon nanotubes (oxCNTs) using various oxCNT QPEI contents ranging from 0.05 to 1.0% w/w and reported that these films exhibited enough optical transparency, advanced mechanical properties, and exceptionally high antibacterial behavior . Kovalchuk and co-workers have produced luminescent PVA composite films containing coal-derived graphene quantum dots (GQDs) by a simple and environmentally friendly solution method.…”
Section: Introductionmentioning
confidence: 99%
“…For the transfer of TiO 2 NRs, PVA was used as a binder as explained at Figure 1d, which can affect the light extraction efficiency of LEDs. 21 Therefore, we compare the three samples: Bare LED(LED-I), an LED with PVA(LED-II), The LEE was obtained from the ratio of the amount of light output power in the air to the generated power in the dipole source. Figure 7 shows the far-field radiation patterns of LED-I, LED-II, and LED-III, which showed similar radiation symmetry, and the calculated LEEs of the LED-I, LED-II, and LED-III were 100%, 135%, and 220%, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To investigate the optical effects of the transferred TiO 2 NR array on LED chips, we measured the light extraction efficiency (LEE). For the transfer of TiO 2 NRs, PVA was used as a binder as explained at Figure d, which can affect the light extraction efficiency of LEDs . Therefore, we compare the three samples: Bare LED­(LED-I), an LED with PVA­(LED-II), and a PVA-coated LED with the TiO 2 NRs array (LED-III).…”
Section: Resultsmentioning
confidence: 99%
“…The photoluminescence of CDs is important because it is widely used in several applications, ranging from sensing, drug tracking, bioimaging, optoelectronic devices [25,48–52] . Several studies have indicated that heteroatom doping can improve the QY values of CDs [8,11,13,53] .…”
Section: Resultsmentioning
confidence: 99%
“…The photoluminescence of CDs is important because it is widely used in several applications, ranging from sensing, drug tracking, bioimaging, optoelectronic devices. [25,[48][49][50][51][52] Several studies have indicated that heteroatom doping can improve the QY values of CDs. [8,11,13,53] To confirm that, in this work, the fluorescence QYs of all CDs were measured using quinine sulfate as a reference (Figure 8).…”
Section: Fluorescence Emissionmentioning
confidence: 99%